(untitled) (Theatrum historiae, 2011)
The Journal of a Visit to Hamburgh and of the Journey from Hamburgh to Goslar (known under the joint title of The Hamburgh Journal) was written in 1798 by Dorothy Wordsworth, sister to Romantic poet William Wordsworth. My interest is in the ways in which the feminine affects the writer’s perception of a foreign com- munity and emotional expression of experiences related thereto, contributing to a feminine modification of 18th-century travel writing standards.